SOCIO-PSYCHOLOGICAL MODEL OF DEVELOPMENT OF A PROFESSIONAL IMAGE OF A TEACHER - Firuza Boturovna, Narzikulov (International Journal of Psychosocial Rehabilitation, 2020)
The article presents a model for the implementation of the system for developing a professional image of a teacher, which is a system consisting of separate, interconnected elements, which ensures the integrity of the process of developing a professional image of a teacher in postgraduate education. The article, an important point in testing the model proposed by the author, presents the introduction of hypothetically predicted pedagogical conditions.